Prevalence and associated risk factors of malaria among adults in East Shewa Zone of Oromia Regional State, Ethiopia: a cross-sectional study - Frew Tadesse; Andrew W. Fogarty; Wakgari Deressa (BMC, 2017)
Abstract Background Malaria is one of the most important causes of morbidity and mortality in sub-Saharan Africa. The disease is prevalent in over 75% of the country's area making it the leading public health problems in the country. Information on the prevalence of malaria and its associated factors is vital to focus and improve malaria interventions. Methods A cross-sectional study was carried out from October to November 2012 in East Shewa zone of Oromia Regional State, Ethiopia. Adults aged 16 or more years with suspected malaria attending five health centers were eligible for the study. Logistic regression models were used to examine the effect of each independent variable on risk of subsequent diagnosis of malaria. Results Of 810 suspected adult malaria patients who participated in the study, 204 (25%) had microscopically confirmed malaria parasites. The dominant Plasmodium species were P. vivax (54%) and P. falciparum (45%), with mixed infection of both species in one patient. A positive microscopic result was significantly associated with being in the age group of 16 to 24 years [Adjusted Odds Ratio aOR 6.7; 95% CI: 2.3 to 19.5], 25 to 34 years [aOR 4.2; 95% CI: 1.4 to 12.4], and 35 to 44 years [aOR 3.7; 95% CI: 1.2-11.4] compared to 45 years or older; being treated at Meki health center [aOR 4.1; 95% CI: 2.4 to 7.1], being in Shashemene health center [aOR = 2.3; 95% CI: 1.5 to 4.5], and living in a rural area compared to an urban area [aOR 1.7; 95% CI: 1.1 to 2.6)]. Conclusion Malaria is an important public health problem among adults in the study area with a predominance of P. vivax and P. falciparum infection. Thus, appropriate health interventions should be implemented to prevent and control the disease.